SHORT STATURE: WHAT IS THE CAUSE IN OUR POPULATION - Ullah, Fahim; Ghaffar, Tahir; Afridi, Ayesha Khan; Ali, Ashfaq; Aamir, Aziz ul hasan (Journal of Ayub Medical College Abbottabad, 2016)
Background: Globally children and adolescents with growth failure are referred to specialized units for evaluation and management. We designed this study to determine the cause of short stature in children and adolescents referred to our endocrine unit for evaluation and further management. Methods: This descriptive cross sectional study was performed in the Department of Endocrine, Diabetes and Metabolic Diseases, Hayatabad Medical Complex, Peshawar. Children and adolescents between 2-20 years with height below 2 SDS or less then 3rd percentile for their age and gender were included while those with kyphoscoliosis, thalassemia major, diabetes mellitus type-1 were excluded. Detailed history was obtained followed by detailed physical examination and a pre-set penal of investigations. Results: 73 children with mean chronological age of 11.75.3±4.06 years, 56.31% boys and 43.83% girls (p<0.05) were included. Mean height was 117.28±17.55 cm, -4.23±2.06 SDS below for this population age group. Mean parental height was 156.87±11.82 cm, mean bone age was 8.56±4.03 years while mean bone age delay was 3.23±1.94 years. Common causes found were variants of normal growth present in 38.35%. Constitutional Delay of Growth and Puberty (CDGP) was found in 13.7%, Familial Short Stature (FSS) in 11.0% while overlapping features of both in other 13.7%. Isolated Growth Hormone Deficiency (GHD) was found in 23.3%, primary hypothyroidism in 9.6% and pan-hypopituitarism in 2.7%. Common non endocrine causes found were Turner's syndrome, rickets, chronic anaemia, bronchial asthma and achondroplasia. Conclusion: Isolated GHD, CDGP and FSS, primary hypothyroidism and Turner's syndrome are the most common causes of short stature in our set up.